2014
DOI: 10.1002/polb.23546
|View full text |Cite
|
Sign up to set email alerts
|

Surface energy gradient driven convection for generating nanoscale and microscale patterned polymer films using photosensitizers

Abstract: The Marangoni effect describes how fluid flows in response to gradients in surface energy. This phenomenon could be broadly harnessed to pattern the surface topography of polymer films if generalizable techniques for programming surface energy gradients existed. Here, a near UV–visible light (NUV–vis) photosensitizer, 9,10‐dibromo‐anthracene (DBA), was doped into thin films of a model polymer, poly(isobutyl methacrylate). After exposure to light through a photomask and heating above the glass transition, therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Perturbations can be created atop a polymer film, on a mesoscopic length-scale in a variety of ways. Unfavourable wetting properties [33][34][35][36][37], electrohydrodynamic instability [38][39][40], Marangoni flow [41][42][43][44], and thermocapillary forces [45][46][47][48][49] can all drive a flat film away from a uniform film thickness. The film viscosity η, surface tension γ, and unperturbed film thickness h 0 , are three parameters that influence the effective mobility of a film, which affects the relaxation of an applied surface perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…Perturbations can be created atop a polymer film, on a mesoscopic length-scale in a variety of ways. Unfavourable wetting properties [33][34][35][36][37], electrohydrodynamic instability [38][39][40], Marangoni flow [41][42][43][44], and thermocapillary forces [45][46][47][48][49] can all drive a flat film away from a uniform film thickness. The film viscosity η, surface tension γ, and unperturbed film thickness h 0 , are three parameters that influence the effective mobility of a film, which affects the relaxation of an applied surface perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…One pathway, as shown in Figure 3a, results in the fluorophore being covalently bound to the polymer chains. [15] The oxidative product formation via light exposure was also confirmed by attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), as shown in Figure S7 (Supporting Information). As more DBA was incorporated into the PS film, stronger characteristic peaks corresponding to the oxidative products were observed after light exposure, increasing the surface energy.…”
Section: Chemical/physical Patterning Mechanismmentioning
confidence: 81%
“…Photosensitizers such as DBA doped into PS films enable significant increases in the feature aspect ratio compared to earlier neat PS work and expand the applicability of the Marangoni patterning method to safer and more readily available light sources (i.e., visible light and sunlight) and other classes of polymers. [15,16] However, Marangonidriven pattern formation on DBA doped PS has not been optimized yet. Therefore, Marangoni-driven patterning of PS films with DBA on a silicon wafer (or a non-shrinking substrate) was systematically investigated.…”
Section: Marangoni-driven Patterning In Polymer Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…73 Kim et al used a photosensitizer to enhance the UV-photopatterning effect and concluded that an endoperoxide of the photosensitizer is a critical reaction intermediate. 74 Adding a photobase generator to a polymer film, Kim et al demonstrated that UV-induced material redistribution could be directed toward either the irradiated or the nonilluminated regions depending on the mode of exposure using either low-intensity and wavelength-selective or high-intensity and broad-band illumination. The authors identified decarboxylation and dehydrogenation reactions as the chemical processes driving the flow.…”
Section: Introductionmentioning
confidence: 99%